Ph stability of four hydrogen peroxide bleaching gels at different time intervals - Ruiz Gamero, Claudia Andrea (2021)
Objective: The aim of this in vitro study was to evaluate the pH of four bleaching agents based on high concentration hydrogen peroxide (30-35%) Whiteness HP Maxx (HPM), Lase Peroxide (LP), Whiteness HP Automixx (HPA) and Dash (DA) in different clinical periods (baseline, 15', 30' and 45'). Materials and methods: 40 specimens (bovine teeth) were divided into 4 groups; one group for each bleaching agent. Each bleaching agent was prepared according to the manufacturer's instructions and was applied on the vestibular surface. The pH of the bleaching agent was measured with a digital pH meter at baseline, 15, 30 and 45 minutes. ANOVA, Friedman and Wilcoxon tests were applied. Results: The pH values showed a trend to decreasing from the initial time of application to the final time, except for the DA group, which showed increasing pH values over time. The HPM group showed significant differences between baseline and the remaining periods. The LP group LP showed significant difference between 15' and the other periods. The HPA group showed significant differences between baseline and the remaining periods. Finally, the DA group, showed a significant difference between baseline and 45’. Conclusions: The pH values of 3 of the bleaching agents decreased over time, with the exception of Dash which increased in the different time periods.